Ecclesiastical Chronotaxes of the Renaissance - Acciarino, Damiano (Renaissance and Reformation / Renaissance et Réforme, 2017)
During the sixteenth century, confessional disputes between Catholics and Protestants became the “battlefield” for determining and shaping the reformed Christian religion. Antiquarian erudition played a key role in this process, acting in accordance with the diverse cultural systems in place, justifying doctrinaire positions, and legitimizing the existence of their institutions. Renaissance chronotaxes illustrate this point particularly well. In this article, for the first time, the ecclesiastical chronotaxes disseminated to Christian scholarly environments throughout Renaissance Europe have been collated and studied. Both the driving forces behind this cultural phenomenon and the methods applied are investigated. The key objective here is to present the first catalogue of these works and to offer valuable material that sheds further light on the cultural, historical, and religious dynamics of the time, which may serve as the basis for further academic debate.